DEVELOPMENT OF CHATBOT LEARNING 4.0 PLATFORM FOR OFFICE ENVIRONMENT IN IMPROVING THE QUALITY OF HUMAN RESOURCES OFFICE MANAGEMENT IN INDONESIA - I Nyoman Suputra; Andi Basuki; Afwan Hariri Agus Prohimi; Ari Gunawan; Afis Baghiz Syafruddin (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The development of the quality of human resources (HR) in office management in Indonesia is becoming increasingly important amid the dynamics of the Industrial Revolution 4.0, which demands adaptation to digital technology in the work environment. Despite various efforts to improve human resource competence, there are still limitations in the effective and efficient application of educational technology for office managerial training needs. This study aims to develop and determine the feasibility of chatbot-based learning in the office environment, especially in improving the quality of office management human resources. The results of the study show that the validation of the material obtained an average score of 85.99% (very valid category), media validation with a score of 87% (very valid category), and validation of the chatbot learning platform with a score of 84.5% (very valid category), indicating that the platform developed is feasible and effective to be used in learning in the office environment. The implications of this study show that the integration of chatbot learning technology can be an innovative solution to improve the quality of human resources in the field of office management in Indonesia, as well as answer the challenges of the Industrial Revolution 4.0.